SETMAR Shorter Isoform: A New Prognostic Factor in Glioblastoma - Lié, Oriane; Virolle, Thierry; Gabut, Mathieu; Pasquier, Claude; Zemmoura, Ilyess; Augé-Gouillou, Corinne (Frontiers in Oncology, 2022)
Recent evidence suggests that the chimeric protein SETMAR is a factor of interest in cancer, especially in glioblastoma. However, little is known about this protein in glioblastoma tissues, and no study has been done to assess if SETMAR could be a prognostic and/or diagnostic marker of glioblastoma. We analyzed proteins of 47 glioblastoma samples coming from a local and a national cohort of patients. From the local cohort, we obtained localized biopsies from the central necrosis area, the tumor, and the perilesional brain. From the French Glioblastoma Biobank (FGB), we obtained three types of samples: from the same tumor before and after relapse, from long survivors, and from very short survivors. We also studied correlations between SETMAR amounts, clinical profiles of patients and other associated proteins (PTN, snRNP70 and OLIG2). In glioblastoma tissues, the shorter isoform of SETMAR (S-SETMAR) was predominant over the full-length isoform (FL-SETMAR), and both SETMAR variants increased from the periphery to the center of the tumor. Data from the FGB showed that SETMAR amounts were not different in the initial tumor and the tumor after relapse. These data also showed a trend toward higher amounts of S-SETMAR in long survivors. In localized biopsies, we found a positive correlation between good prognosis and large amounts of S-SETMAR, only in the perilesional area (p=0.007). This is the main result presented here: survival in glioblastoma is correlated with amounts of S-SETMAR in perilesional brain, which should be considered as a new relevant prognosis marker.